Chromosomal differentiation of Tribe Cestreae (Solanaceae) by analyses of 18-5.8-26S and 5S rDNA distribution - Urdampilleta, Juan Domingo (2014)
Tribe Cestreae is monophyletic with three genera: Cestrum, Sessea, and Vestia. Karyotypically, it is outstanding within Solanaceae by several features: (1) basic number x = 8, (2) large chromosome sizes, (3) complex heterochromatin patterns, (4) occurrence of B-chromosomes (Bs) in Cestrum with particular banding patterns and rDNA sites distribution, and (5) absence of Arabidopsis-type telomeres. Seventeen South American Cestreae species from the three genera were studied using fluorescence in situ hybridization (FISH) with ribosomal DNA regions (5S and 18-5.8-26S) as probes, with the aim of recognizing specific or group-specific chromosomal markers and analyzing karyotype diversity in a systematic and evolutionary context. The first chromosome number report for Cestrum euanthes, C. kunthii, C. lorentzianum, and C. tomentosum is included. Variation in number and distribution of rDNA loci was observed among the species, concerning both As and Bs chromosomes. Despite the constancy of the karyotype and numbers of rDNA loci, the mapping of 18-5.8-26S and 5S rDNA loci allowed to differentiate Cestreae genera and species groups within Cestrum, highlighting the importance of these markers as cytotaxonomic character in this tribe.